Fatores de risco para o câncer de colo e lesões cervicais por papilomavirus humano - Bezerra, Saiwori de Jesus da Silva (2007)
Despite all scientific development in health area, many old problems still exist. Among them, we have cervical cancer, one of them able of prejudice and cure if detect previously. One of the known risk factors of cervical cancer is the early sexual actively, multiple partners, tabagism, long use of oral contraceptive, STD, and particulary, a HPV, present in most of 90% of cases. This word has the objective of checking the association between presence and cervical lesions features by HPV related to the risk factors to cancer cervical. To that, a prevalence study was made, using quantitative method including 157 women, in a period of June till September 2006, in a health center of Fortaleza city. It was used a formulary comprising: personal date, result of exam (pH, cytology, VIA, cervicograph) and risk factors. VIA, cervicograph and cytology were the following changed exams percentuals: 43,3%, 10,19% e 3,2% respectively. Cervicographs was positive in 20,5% of women with changed cytology. About lesion features, most of the sample (81%) showed colorimétricas changing reactive to acetic acid of light white color (40%) medium white (40%). The variables associated to the cervical lesion in VIA were: teenagers (bellow 20 years); one or more concurrent sexually in last 3 months; low scholar level; low economic power; deliveries; STD presence; contraceptive use; tabagism; QTF; drinking habitude; number of drinks; vaginal content; inflammation and pH over 4,5. The cervicograph showed as correlated factors: yang below 30 years old; low scholar level; ; low economic power; not use of prevent exam; drinking habitude; number of drinks per day and pH over 4,5. Cytology showed: yang below 30 years old; low scholar level; low economic power; QTF; contraceptive time; ; number of drinks per day; pH over 4,5 and high level of pH. Conclusion shows that factors risk may be controlled, having the necessity of an education work appropriated to the social-cultural reality of every individual and specifically control ways that can respect every individual particularity. The knowledge here displayed snakes possible to the nurse works in every predisposition cause and interposing in prevent methods to this pathology.